2020
DOI: 10.1017/cjn.2020.44
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Traumatic Acute Interhemispheric Subdural Hematoma

Abstract: ABSTRACT:Object:Interhemispheric subdural hematomas (IHSDHs) are thought to be rare. Surgical management of these lesions presents a challenge as they are in close proximity to the sagittal sinus and bridging veins. IHSDHs are poorly characterized clinically and their exact incidence is unknown. There are also no clear guidelines for the management of IHSDH.Methods:This is a retrospective review of all admitted patients with a diagnosis of traumatic brain injury over a 4-year period at a Level I trauma centre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…It is still one of the main causes of traumatic brain injury death [ 21 ]. With the increase of traffic accidents and falling accidents, the incidence of this disease is increasing year by year [ 1 ]. The brain function of patients with TSDH is seriously damaged, and there are many kinds of dysfunction, which is a serious threat to patients' health and life safety [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still one of the main causes of traumatic brain injury death [ 21 ]. With the increase of traffic accidents and falling accidents, the incidence of this disease is increasing year by year [ 1 ]. The brain function of patients with TSDH is seriously damaged, and there are many kinds of dysfunction, which is a serious threat to patients' health and life safety [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic subdural hematoma (TSDH) is a common disease in neurosurgery [ 1 ]. The pathogenesis of this disease is mainly that the patient's head is violently hit, which causes the dura mater of his brain tissue to shift.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people with enlarged subdural space due to cerebral atrophy, excessive alcohol consumption, anticoagulant medication, and coagulopathy were reported to be risk factors for AISDH. [1,4] Léveillé et al [5] reported that AISDH was found in 420 (35.5%) of 1182 cases of traumatic acute subdural hematoma. However, most of the cases consisted of only a small subdural hematoma in the interhemispheric fissure, which arose secondarily from other traumatic injuries such as acute subdural hematoma in the convexity, subarachnoid hemorrhage, and cerebral contusion, and needed no surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the cases consisted of only a small subdural hematoma in the interhemispheric fissure, which arose secondarily from other traumatic injuries such as acute subdural hematoma in the convexity, subarachnoid hemorrhage, and cerebral contusion, and needed no surgery. [5] Wang et al [9] also reported that surgery was infrequently required for AISDH and that surgical cases of AISDH were identified in only 21 (0.3%) out of 6840 cases of traumatic brain injury. In the present operative case of AISDH, subdural hematoma was found not only in the interhemispheric fissure but also in the convexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation